2016
DOI: 10.1055/s-0036-1594296
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Controlled Mobilization after Lower Extremity Free Flaps—Pushing the Limits of Time and Intensity

Abstract: The current standard to gradually adapt the fragile perfusion in lower extremity free flaps to an upright posture is the dangling maneuver. This type of flap training neither fits the orthostatic target load of an upright posture, nor does it assist in mobilizing the patients effectively. In this study, we quantitatively analyzed training effects of an early and full mobilization on flap perfusion. A total of 15 patients with gracilis flaps for distal lower extremity reconstruction were included. Flap training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Thereafter, venous pooling took over, resulting in a decrease of StO 2 [ 4 , 19 ]. In the current study, this increase was not observed and was more in line with the study of Dornseifer et al On POD 3 and 4, they observed this increase in StO 2 as well, but on POD 5 this effect disappeared [ 20 ]. Furthermore, the saturation values of the contralateral leg were lower during the entire measurement than the saturation values of the free flap.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thereafter, venous pooling took over, resulting in a decrease of StO 2 [ 4 , 19 ]. In the current study, this increase was not observed and was more in line with the study of Dornseifer et al On POD 3 and 4, they observed this increase in StO 2 as well, but on POD 5 this effect disappeared [ 20 ]. Furthermore, the saturation values of the contralateral leg were lower during the entire measurement than the saturation values of the free flap.…”
Section: Discussionsupporting
confidence: 93%
“…In the studies of Dornseifer et al and Ridgway et al, the dangling time was set at five minutes per day (dangling period was POD 7 until discharge and POD 3 until POD 9, respectively). Both found a significantly higher minimum StO 2 every following POD [ 19 , 20 ]. This is comparable with the study of Kolbenschlag et al They started dangling at POD 6, three times per day for 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in postoperative oedema 20 and pain reduction during dangling 9 were reported. Near-infrared spectroscopy 9,19,22 and micro-dialysis monitoring 16 were used to measure flap perfusion parameters of compressed flaps during dangling, showing a lower drop in tissue oxygenation when compared to unwrapped limbs.…”
Section: Resultsmentioning
confidence: 99%
“…Dangling protocols vary widely in their length and their level of detail and prescriptiveness, with dangling regimes varying in length from as little as 1-2 days to as long as 12 days [1,7] . Some units have made their dangling protocols public and shown encouraging results that early weight-bearing protocols can improve standardization of care and reduce hospital stay without an increase in complications [23] . Other research efforts have examined the use of techniques such as compression dressings and tilt-tables to help "train" the flap to the conditions experienced in dependency [1,24] .…”
Section: Discussionmentioning
confidence: 99%